Successful Salvage of Delayed Venous Congestion After DIEP Flap Breast Reconstruction - Katira, Kristopher (Eplasty, 2019)
Objective: Failure rates of microvascular autologous breast reconstruction are reportedly low. When failure of the microvascular anastomoses does occur, it is most likely to be salvaged if detected early. Flap compromise or venous congestion occurring several weeks later is uncommon and with significantly lower salvage rates. Methods: We present a unique case of delayed venous congestion of a single-perforator deep inferior epigastric perforator flap breast reconstruction in which the usual pedicle thrombosis was not identified. Presentation of the flap compromise occurred 72 hours postoperatively and again in the delayed setting 5 weeks after surgery, from suspected compression at the perforator level. Results: The deep inferior epigastric perforator flap was successfully salvaged with conservative measures, and the flap healed without fat necrosis or further complication. Conclusion: This case highlights the higher risk of flap compromise with reconstructions in a radiated field and potentially with single-perforator flaps.